Training in the Manufacture of Softener Fragrance Aroma Therapy in Tembung Village, District Percut Sei Tuan - Marpongahtun; Andriayani; Pratama, Agung; br Sembiring, Helmina; Prayugo, Aniza Salviana; Daulay, Amru (Talenta Publisher, 2023)
Tembung Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, is a densely populated area. There are more than 200 laundry businesses. The potential for laundry business actors to produce softener and aromatherapy fabric softener has been hit very hard. However, the villagers, especially laundry business actors, do not know how to make these products. Making aromatherapy softeners independent will provide added value to the laundry business actors and villagers regarding economic costs and the transfer of knowledge of technology (science and technology commercialization). Therefore, the University of North Sumatra community service team wants to commercialize science and technology in making aroma softening therapy. The method used in this activity is the selection of partner locations, training, monitoring, and evaluation. The results of the questionnaire gave a value of 95% Participants were interested in training to produce aromatherapy softeners independently and took the initiative to make the results of this training a new opportunity.